Saul Bass : Anatomy of Film Design. - Horak, Jan-Christopher. (Lexington : The University Press of Kentucky, 2014)
Saul Bass defined an era. He designed movie posters, studio publicity, credit sequences for films, and corporate logos from the 1940s to the 1990s, and he was an Academy Award-winning filmmaker. As a result, Bass changed the look of both film advertising and cinema itself. Bass's advertising, poster designs, and title sequences for Hollywood feature films were extremely innovative in terms of their formal design, use of iconography, and narrative content. Bass influenced not only other studio publicity designers and filmmakers but also a whole generation of young designers.
Introduction: Qui êtes-vous, Saul Bass? -- Designer and filmmaker -- Film titles: theory and practice -- Creating a mood: pars pro toto -- Modernism's multiplicity of views -- The urban landscape -- Journeys of discovery: seeing is knowledge -- Civilization: organizing knowledge through communication.
Print version record.
Includes bibliographical references, filmography and index.
JSTOR
Keywords: Bass, Saul -- Criticism and interpretation; Bass, Saul; PERFORMING ARTS -- Film & Video -- History & Criticism; ART -- Techniques -- Drawing; Criticism, interpretation, etc